Surface texture depth measurements on some British roads - Roe, P. G.; Tubey, L. W.; West, Graham; Transport and Road Research Laboratory. Pavement Materials and Construction Division (Crowthorne, Berkshire : Pavement Materials and Construction Division, Highways Group, Transport and Road Research Laboratory, 1988)
"The high-speed texture meter (HSTM), which uses a laser-based contactless sensor, has been developed to enable texture depth to be measured on a routine basis on large road networks at normal traffic speeds"--Abstract.
Bibliography: p. 16.
Keywords: Pavements -- Testing -- Great Britain